2014
DOI: 10.3109/02813432.2014.972046
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with sore throats in relation to guidelines: An interview study in Sweden

Abstract: Objective. To explore how a group of Swedish general practitioners (GPs) manage patients with a sore throat in relation to current guidelines as expressed in interviews. Design. Qualitative content analysis was used to analyse semi-structured interviews. Setting. Swedish primary care. Subjects. A strategic sample of 25 GPs. Main outcome measures. Perceived management of sore throat patients. Results. It was found that nine of the interviewed GPs were adherent to current guidelines for sore throat and 16 were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
2
27
0
1
Order By: Relevance
“…Similar findings were reported by Hedin et al (2014), who found that one-third of primary care physicians did not remember the Centor criteria and were therefore not able to use them. They added that while individual signs are not sufficient for the diagnosis of acute pharyngitis caused by group A streptococci, the Centor score is considered a well-calibrated decision rule for assessing the probability of group A streptococci.…”
Section: Results:-supporting
confidence: 88%
See 3 more Smart Citations
“…Similar findings were reported by Hedin et al (2014), who found that one-third of primary care physicians did not remember the Centor criteria and were therefore not able to use them. They added that while individual signs are not sufficient for the diagnosis of acute pharyngitis caused by group A streptococci, the Centor score is considered a well-calibrated decision rule for assessing the probability of group A streptococci.…”
Section: Results:-supporting
confidence: 88%
“…They added that while individual signs are not sufficient for the diagnosis of acute pharyngitis caused by group A streptococci, the Centor score is considered a well-calibrated decision rule for assessing the probability of group A streptococci. (17) In the Democratic Republic of Congo, Thriemer et al (2013) reported that sources of physicians' knowledge related to antibiotic prescribing included pharmaceutical companies (73.9%), antibiotic guidelines (66.3%), university courses (63.6%), internet-sites (45.7%) and WHO guidelines (26.6%). (18) This study showed that the highest participants' answer regarding the best antibiotic used in the treatment of acute bacterial pharyngitis was penicillin (90.7%), with oral administration as the best route for administration (92.1%) for 5-7 days (72.9%).…”
Section: Results:-mentioning
confidence: 99%
See 2 more Smart Citations
“…Swedish interview studies have indicated that high prescribing doctors were not aware of or not updated on the national guidelines for tonsillitis [31], which may explain the current findings. Finally, excessive use of CRP as a diagnostic tool, was noted, particularly in association with common cold and sore throat, which is not according to guidelines.…”
Section: Discussionmentioning
confidence: 88%